Daptomycin dosing in obese patients: analysis of the use of adjusted body weight versus actual body weight. (January 2019) - Fox, Ashley N.; Smith, Winter J.; Kupiec, Katherine E.; Harding, Stephanie J.; Resman-Targoff, Beth H.; Neely, Stephen B.; White, Bryan P.; Owens, Ryan E.
Background: Food and Drug Administration–approved daptomycin dosing uses actual body weight, despite limited dosing information for obese patients. Studies report alterations in daptomycin pharmacokinetics and creatine phosphokinase elevations associated with higher weight-based doses required for obese patients. Limited information regarding clinical outcomes with alternative daptomycin dosing strategies in obesity exists. Objective: This study evaluates equivalency of clinical and safety outcomes in obese patients with daptomycin dosed on adjusted body weight versus a historical cohort using actual body weight. Methods: This retrospective, single center study compared equivalency of outcomes with two one-sided tests in patients with body mass index ⩾30 kg/m 2 who received daptomycin dosed on actual body weight versus adjusted body weight. The primary outcome was clinical failure. Secondary outcomes included 90-day readmission and 90-day mortality. A combined safety endpoint included creatine phosphokinase elevation, patient-reported myopathy, and rhabdomyolysis. Results: A total of 667 patients were screened for inclusion; 101 patients were analyzed with 50 in the actual body weight cohort and 51 in the adjusted body weight cohort. The two regimens were statistically equivalent for clinical failure (2% actual body weight versus 4% adjusted body weight; p < 0.001 for equivalency). The two regimens were also statistically equivalent for 90-day mortality (6% actual body weight versus 4% adjusted body weight; p = 0.0014 for equivalency). Limitations include single center, retrospective design, and sample size. Daptomycin dosing intensified throughout the study period. Conclusion: The two daptomycin dosing cohorts were statistically equivalent for both clinical failure and 90-day mortality. More data are needed to assess outcomes with higher (⩾8 mg/kg/day) daptomycin doses in this patient population.